2019
DOI: 10.1101/613596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Spatiomolecular Map of the Striatum

Abstract: The striatum is organized into two major outputs formed by striatal projection neuron (SPN) subtypes with distinct molecular identities. In addition, the histochemical division into patch and matrix compartments represents an additional spatial organization, proposed to mirror a functional specialization in a motor-motivation dimension. To map the molecular diversity of SPNs in the context of the patch and matrix division, we genetically labeled mu-opioid receptor (Oprm1) expressing striatal neurons and per… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Finally, it is worth discussing OPRM1, the gene for the µ-opioid receptor. Many studies use OPRM1 as a marker for striosomes (Märtin et al, 2019). Our data revealed that OPRM1 was upregulated in the striosome, as predicted, but the upregulation was not as dramatic as we expected.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, it is worth discussing OPRM1, the gene for the µ-opioid receptor. Many studies use OPRM1 as a marker for striosomes (Märtin et al, 2019). Our data revealed that OPRM1 was upregulated in the striosome, as predicted, but the upregulation was not as dramatic as we expected.…”
Section: Discussionsupporting
confidence: 84%
“…The Sepw1 NP67 line has been previously used to study patch connectivity [28,54] and activity [45]. Other recent studies have utilized alternative Cre lines to target patches, including Mash1-CreER [44], 599-CreER [63], or Oprm1-Cre [64], though each of these lines also has some off-target labeling of exo-patch or matrix neurons. Thus, while the current work suggests lesions preferentially targeting patches impair aspects of habitual behavior, we cannot rule out the contribution of exo-patch neurons in this process.…”
Section: Discussionmentioning
confidence: 99%
“…4E, Sup.Fig. 5C) [53,54]. Cell cycle position estimation analysis (estimating a continuous cell-cycle pseudotime by principal component analysis of cell-cycle genes) showed that most cells in cluster 3 (NPC), cluster 4 (NB), and some cells in cluster 8 (ElC) were actively dividing cells, while cells of other clusters were predicted to be in the G1-phase (Sup.Fig.…”
Section: Weighted Gene Co-expression Network Analysis and Gene Ontolo...mentioning
confidence: 99%